To Buy or Not to Buy? Investing in a Dissertation in Ukraine - Osipian, Ararat L. (International Higher Education, 2021)
In addition to widespread and globalized academic essay mills, doctoral degree fraud is becoming an issue. In Ukraine, dozens of firms offer ghostwritten dissertations for sale. Aspirant doctorate holders face the dilemma: to buy, or not to buy, a ghostwritten dissertation. Despite the mounting costs of a doctorate, it is a union card that brings job security and snowballing benefits in large increments to those who decide to invest in a ghostwritten dissertation.